Facebook for intercultural communication: The foreign students’ experience - Raja Zainal Hassan, Raja Rodziah; Hassan, Nor Azlili; Sallehuddin, Iza Sharina; Abdul Aziz, Nik Norazira (Universiti Utara Malaysia Press, 2020)
Computer-mediated communication is an integral part of how people communicate in today’s modern society. The impact of social media on intercultural competency is a new territory that is beginning to interest scholars and researchers. Part and parcel of a foreign university student’s experience in a host country are managing cultural differences. Understanding how foreign university students use computer-mediated communication will provide insights into the impacts of social media (Facebook) on intercultural learning experiences. The aims of this study are: 1) to analyse the experience of foreign university students in using Facebook to communicate with their local peers 2) to examine Facebook usage pattern(s) among foreign university students in Malaysia, and; 3) to determine the level of intercultural competency among foreign university students in Malaysia. The study employs the Intercultural Sensitivity Scale (ISS) developed by Chen and Starosta (2000) in analysing how foreign university students in Malaysia use Facebook as part of a platform in learning and coping with cultural differences. This study analyses data from a survey of 210 foreign university students in Klang Valley, Malaysia. The findings from this study illustrated that the majority of foreign university students enjoy communicating with their local peers who are from different cultures using Facebook. The findings highlight that foreign university students are confident when communicating with their local friends and they are culturally competent. This is examined from the online interactions with their local peers and the Facebook usage pattern developed from their experience.